Determinant Factors of the Household Poverty Probability: Study on Household around the Taman Nasional Kerinci Sebelat (TNKS) Lebong Regency - Gustin Rizki Utariyanto; Ketut Sukiyono; Septri Widiono (AGRITROPICA : Journal of Agricultural Sciences, 2020)
This research aims to determine the factors that influence the probability of occurrence of poverty of households around Taman Nasional Kerinci Seblat (Kerinci Sebelat National Park (TNKS) Lebong District. The location of this research selected purposively by categorizing the 6 villages into 3 typologies, namely, Sawah dominance, plantation Dominance, and rice fields and plantation. From each village, 20 households as respondents were selected randomly, so the total respondents were 120 households. Sayogjo poverty line was applied to determine household poverty status. In examining the factors that affect the probability of the household poverty, a logit model is applied. From the analysis, land area ownership is the main factor influencing the occurrence probability of poverty of households, while education level, number of family dependents, and household head age are not.